Pengaruh Pijat Bayi Terhadap Lama Tidur Bayi Usia 3-6 Bulan di Desa Jemawan Kecamatan Jatinom Kabupaten Klaten - Henik Istikhomah; Devi Dwi Kurniasari; Siswiyanti Siswiyanti (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Sleep is prime priority for baby, because when this moment occurs repair neuro-brain and more or less 75% of growth hormone are produced. Considering the importance of sleep time for baby development, baby’s sleep needs must be fulfilled in order not to adversely affect growth and development. One of the way to fulfill baby’s sleep needs is baby massage. When baby massaged will increase serotonin secretion that will suppress the activity of the reticulation-activating system and causing sleepy. Purpose this study to knowing the effect of baby massage to the length of sleep of baby ages 3-6 month in Jemawan Village, Jatinom Sub-District, Klaten District. Methods: Quasy eksperiment research with one group pretest-posttest design. Sampling using saturated sampling technique with 32 babies. Bivariate analysis using non parametric statistic Wilcoxon test with an error rate of 5%. Baby massage is performed of baby ages 3-6 month throughout the baby’s body for 30 minutes, baby massage is doing 2 times a week in 4 weeks.Results: This study show results that the length of sleep of baby before doing massage is mostly less than 13 hours as much as 18 babies (56,25%) and the length of sleep of baby after doing massage is normal 13-15 hours as much as 27 babies (84,38%). The result of Wilcoxon test is p = 0,000 (p <0,05) that Ha accepted.Conclusion: There is effect of baby massage to the length of sleep of baby ages 3-6 month in Jemawan Village, Jatinom Sub-District, Klaten District.